Chemical composition and ability of essential oils from six aromatic plants to counteract lipid oxidation in emulsions - TCOBO, Fidèle; ALITONOU, GUY ALAIN; SOUMANOU, MANSOUROU MOHAMED; Barea, Bruno; BAYRASY, Christelle; LAGUERE, Michael; LECONTE, Jérôme; VILLENEUVE, Pierre; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2014)
Essential oils with antioxidant properties are of increasing interest in West Africa where there are many antioxidant rich plants. The objective of this study was to determine the essential oil extracted from six native plants (Lippia multiflora, Lippia rugosa, Monodora tenuifolia, Ocimum gratissimum, Pimenta racemosa, Cymbopogon citratus) extracted by hydrodistillation from local plants in Benin. These samples were also evaluated for their antioxidant capacity using the conjugated autoxidizable triene (CAT) assay performed in stripped tung oil-in-water emulsion. The essential oil of P. racemosa, containing high amounts of chavicol (10.3 %) and eugenol (54.5 %), showed the strongest antioxidant activity, followed by that from O. gratissimum containing large amounts of thymol (50.2 %). The essential oil extracted from M. tenuifolia exhibited a moderate antioxidant activity. This essential oil is primarily composed of sesquiterpene alcohols such as acadinol (20.5 %), its isomer, a-muurolol (14.7 %), and germacrene D-4-ol (16.8 %). Essential oils from L. multiflora, L. rugosa and C. citratus oils showed poor ability to protect tung oil from oxidation. Finally, essential oils containing phenolic compounds and, in a lesser extent, sesquiterpene alcohols, exhibited the highest CAT values indicating that these compounds are the key determinants of the antioxidant activity of these essential oils in oil-inwater emulsions. (Résumé d'auteur)
Keywords: Huile essentielle; Plante à huiles essentielles; Émulsion; Antioxydant; Composition chimique; Lipide; Oxydation; Cymbopogon citratus; Pimenta racemosa; Monodora tenuifolia; Lippia; Ocimum